Recent Findings and Methodologies in Economics Research in Environmental Justice - Lucas Cain; Danae Hernandez-Cortes; Christopher Timmins; Paige Weber (Center for Economic Studies and ifo Institute (CESifo), 2023)
This review synthesizes economics-oriented research in environmental justice with a focus on the last decade. We first categorize this literature into broad areas of inquiry and review main findings. Then, we review recent advances in data and methodologies that have allowed for new study designs and research questions. After identifying breakthroughs, we offer some guidance on how to continue to advance research in this area.
Keywords: Q56; Q53; Q54; 330; environmental justice; procedural justice; equity; distributional impacts